Sequence and secondary structure of the mitochondrial 16S ribosomal RNA gene of Ixodes scapularis. Issue 1 (February 2015) - Krakowetz, Chantel N.; Chilton, Neil B.
Abstract: The complete DNA sequences and secondary structure of the mitochondrial (mt) 16S ribosomal (r) RNA gene were determined for six Ixodes scapularis adults. There were 44 variable nucleotide positions in the 1252 bp sequence alignment. Most (95%) nucleotide alterations did not affect the integrity of the secondary structure of the gene because they either occurred at unpaired positions or represented compensatory changes that maintained the base pairing in helices. A large proportion (75%) of the intraspecific variation in DNA sequence occurred within Domains I, II and VI of the 16S gene. Therefore, several regions within this gene may be highly informative for studies of the population genetics and phylogeography of I. scapularis, a major vector of pathogens of humans and domestic animals in North America.